Caries and Oral Health related Quality of Life Amongs Thalassemia Major Children - Oktadewi, Fitri Diah; Purnama, Ryana Budi; Taqwim, Ali; financia, dwi cinthya; cahyaningrum, nadya elsa (Kesmas Indonesia, 2024)
Patients with thalassemia generally have high caries rates. Dental caries in children can have a negative impact on daily activities and quality of life. Researchs on the comparison of caries and oral health related quality of life between thalassemia children and healthy children provides inconsistent results. The aim of this study was to compare dental caries and oral health-related quality of life between children with thalassemia major and healthy children. This study was a cross sectional study involving 17 children with thalassemia mayor and 22 healthy children who were selected by purposive sampling in Banyumas, Central Java. Caries was assessed using the DMFT/deft index through digital panoramic radiographs and clinical photographs of the oral cavity. Oral health-related quality of life was assessed using the Indonesian version of the Child Oral Health Impact Profile-SF 19 questionnaire. DMFT /deft scores in thalassemia major children and healthy children were 2.64 ± 2.06 and 2.23 ± 1.38, respectively. OHRQoL scores in thalassemia major and healthy children were 56.82 ± 10.35 and 56.73 ± 7.70, respectively. There was no significant difference between DMFT/deft scores and oral health-related quality of life scores between thalassemia major children and healthy children (p=0.663 and p=0.974, respectively). Nevertheless, oral health in children with thalassemia should be improved.